Podział terytorialny specjalny a obszar specjalny - Zacharczuk, Piotr (PRAWO i WIĘŹ, 2025)
here is no legal definition in administrative law for the terms „special territorial division” and „special area”. These terms are also not a legal term according to the current legislation. Using the existing achievements of administrative law doctrine, in particular those relevant to the current normative reality, it is possible to develop definitions of these semantically distinct concepts. Territorial divisions, including special territorial divisions, fall within the scope of political-organisational administrative law, as special territorial divisions are created primarily to define the territorial scope of action of non-integrated state administration or other territorial organisational units of administrative entities. A special territory, on the other hand, is a legal institution of substantive administrative law, the essence of which lies primarily in the relationship of an isolated specific space to a special legal regime that limits or extends the existing general legal order.